Mini C-Arm Fluoroscopy: Does Its Configuration Matter for Radiation Exposure to the Surgeon?. (September 2018) - Chapman, Talia; Martin, Dennis P.; Williamson, Christopher; Tinsley, Brian; Wang, Mark L.; Ilyas, Asif M.
Background: The risk of occupational radiation exposure to the surgeon associated with the use of a mini C-arm has yet to reach a wide consensus. Using a distal radius fracture surgery model, we tested the hypothesis that radiation exposure to the surgeon's critical body parts is independent of mini C-arm configuration.Methods: An anthropomorphic mannequin (representing the upper body of a 60" male surgeon) was seated at a hand table as if operating on a volar-plated wrist Sawbone model. Thermoluminescent dosimeters measured radiation exposure to the surgeon's eyes, thyroid, chest, hand, and groin from a mini C-arm fluoroscopy unit in 3 commonly used configurations: vertical (source above table), inverted (source below table), and horizontal (with beam parallel to table surface). The fluoroscope scanned the wrist model for 15 continuous minutes in triplicate for each orientation.Results: Radiation to the hand was significantly greatest in all mini C-arm positions compared with all other anatomic sites irrespective of C-arm position. Hand radiation exposure was greatest in the horizontal position (2887.09 mrem), versus the vertical and inverted positions (59.79 mrem, 31.10 mrem, P < .001). Eye radiation exposure was significantly greater in the inverted position (2.33 mrem) compared with the vertical (0.67 mrem, P = .024), and horizontal positions (0.33 mrem, P = .012). No significant difference in radiation exposure was found at the thyroid, chest, and groin sites, at each of the 3 C-arm configurations.Conclusions: The model's hand received almost 1000 times more radiation exposure than all other anatomic sites with statistically greatest radiation exposure sustained in the horizontal position. Eye radiation exposure with the C-arm in the inverted position (below the table) was also significantly greater.